Lactobacillus lactis CKDB001 ameliorate progression of nonalcoholic fatty liver disease through of gut microbiome: addendum - Lee, Na Young (Gut Microbes, 2020)
According to our recent study (N.Y. LEE et al. Gut Microbes 2020; 11:882–99.)(1), we reported that Lactobacillus and Pediococcus ameliorate progression of nonalcoholic fatty liver disease through modulation of the gut microbiome. According on the analysis method (Previous: 16s rRNA sequencing and Recent: whole gene sequencing), the probiotics named Lactobacillus bulgaricus that we used in the experiment was identified as Lactobacillus delbrueckii subsp. bulgaricus through 16s rRNA sequencing analysis. Recently, we performed a clearer analysis with whole gene sequencing to proceed with the clinical trial, it was identified as Lactobacillus delbrueckii subsp. lactis by whole gene sequencing. Therefore, we inform that the subspecies have been changed to lactis through WGS. Read L. bulgaricus in the previous paper as L. lactis. In this addendum, the results of the change to L. lactis are summarized, and descriptions have been added to Materials & methods and Discussion.